Chemical constituents of Exoecaria agallocha Linn. - Perez, Judy (Animo Repository, 2019)
Chemical investigation of the dichloromethane extracts of the mangrove, Exoecaria agallocha Linn. has led to the isolation of alkyl ferulates (1), lupeol (2), a mixture of 3-epi-α-amyrin (3) and 3-epi-β-amyrin (4) in about 2:3 ratio, and agallochaol K (5) from the bark; taraxerol (6), epi-taraxerol (7) and chlorophyll a from the leaves; and a mixture of compounds 3 and 4 in about 1:2 ratio, squalene, olean-12-en-3-one (8) and fully epoxidized linoleic acid from the twigs. The structures of compounds 5 and 7 were elucidated by extensive 1D and 2D NMR spectroscopy and confirmed by comparison of their NMR data with those reported in the literature. The structures of the other compounds were identified by comparison of their NMR data with literature data. © 2019 Chemical Publishing Co. All rights reserved.